Transcriptome Analysis in Human Breast Milk and Blood after Inactivated or Attenuated Influenza Immunization. (4th October 2017) - Schlaudecker, Elizabeth P; Goll, Johannes; Jensen, Travis; Petrie, Carey; Gelber, Casey; Dexheimer, Phillip; Steinhoff, Mark; Bernstein, David I
Abstract: Background: The goal of this study was to identify transcriptomic signatures (RNA-Seq) in human peripheral blood mononuclear cells (PBMCs) and breast milk lymphocyte cells (BMLCs) in response to trivalent inactivated influenza vaccine (TIV) or live attenuated influenza vaccine (LAIV). Methods: We performed a randomized, double-blind study in breastfeeding women who received either LAIV and intramuscular placebo, or TIV and intranasal placebo. A subset of subjects with available samples (LAIV, n = 10 and TIV, n = 6) was used for this study. Human milk was collected on days 0, 2, 8, and 28, and blood samples were collected on days 0 and 28. PBMC and BMLC RNA was extracted for RNA-Seq and differentially expressed (DE) gene analysis. Results: We identified a total of 382 DE BMLC genes in the LAIV group, most of which were up-regulated at day 28. DE genes were preferentially involved in innate immune signaling pathways including cytokine-cytokine receptor interaction, TNF signaling, and NF-kappa B signaling. For TIV, 3 DE genes were identified of which 2 ( IL1A and IL1B ) overlapped with LAIV. Response time trends for co-expressed gene clusters by vaccine group showed that LAIV generally induced an early (day 2) up-regulation of innate immune signaling pathway genes, while TIV induced peak innate immune signaling gene responses ahead of LAIV (day 8 vs. day 28). A group of known interferon-alpha/β-inducible genes ( IFIT3, OAS3, IFI44L, MX1, OAS2, IFIT1, IFI6 ) showed higher responses at day 2 for TIV but stronger peak levels by day 28 for the LAIV group (Fig 1). While no such innate immune signaling responses were observed in PBMCs at day 28, we identified an up-regulation of IgG gene (IGHG1 and IGHG3 ) expression in the TIV group (Fig 2). Conclusion: We observed increased innate immune signaling responses in BMLC but not in PBMC at day 28 for the LAIV group. We hypothesize that breastfeeding extends the innate response to LAIV via mucosal immunity. Gene cluster time trends indicated an earlier innate immune signaling response for TIV. The day 28 increase in IGHG3 gene expression levels in TIV group PBMCs was correlated with corresponding increases in serum ELISA IgG titers for the influenza B antigen (Fig 3). Additional studies are required to investigate the differences in innate response signaling seen for BMLC and PBMC in this study. Disclosures: All authors: No reported disclosures.